Relationship Between Loneliness and Fear Without a Smartphone (Nomophobia) Among TikTok Users - Sikumbang, Laila Husna; Dewi, Fransisca Iriani Roesmala (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The use of social media has become an important part of everyday life, especially for students who use it for entertainment, communication, learning, and information seeking. High intensity of use is often associated with various psychological problems, including feelings of loneliness and dependence on smartphones, also known as nomophobia. One of the platforms widely used by students today is TikTok, which provides short, interactive, and easily accessible video content. This study aims to determine the relationship between loneliness and nomophobia among students who use the TikTok application. A correlational quantitative approach was used, involving 163 students aged 18 to 23 years who actively use TikTok. Measurements were taken using the UCLA Loneliness Scale to measure loneliness levels and the Nomophobia Questionnaire or NMP-Q to measure nomophobia levels. Data analysis was performed using Pearson's correlation test to determine the direction and strength of the relationship between variables. The results showed a correlation coefficient of r = 0.15 with p < 0.05, indicating a significant positive relationship between loneliness and nomophobia. These findings suggest that students with higher levels of loneliness tend to exhibit higher levels of nomophobia. This study is expected to contribute to understanding the psychological dynamics of students in their use of social media and serve as a reference for further research.